DESIGN OF AUTOMATIC WATERING SYSTEM FOR JASMINE FLOWER ORNAMENTAL PLANTS USING IOT-BASED MICROCONTROLLER - Hartesa Osi; Ali Nurdin; Suroso (RADJA PUBLIKA, 2025)
The rapid development of information technology has provided convenience in various aspects of human life, including in the fields of agriculture and ornamental plant care. One of the technologies that is currently developing is the Internet of Things (IoT), which allows the integration of physical devices with internet networks to automate and monitor in real time. This study aims to design and build an automatic watering system for jasmine ornamental plants based on a microcontroller using the Arduino IoT Cloud platform. This system is designed to help homeowners care for ornamental plants more efficiently, especially in terms of watering which has so far been done manually. With the help of soil moisture and temperature sensors, this system can monitor the environmental conditions of plants and water them automatically as needed. Through the Arduino IoT Cloud application that can be accessed via smartphone, users can also monitor and control the system remotely. It is hoped that this system can overcome the limitations in manual plant care, as well as increase the effectiveness and efficiency in maintaining the health of jasmine ornamental plants.